"Kontynenty - Nowy Merkuriusz" (styczeń 1959 - luty 1961) - Moczkodan, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
The article is a discussion – mainly from the editorial-programme side – of the history of the fourth mutation of the magazine published in London by a poetic group called “Continents”. In this outline goals set by the changing editorial board are indicated and the difficulties faced while realizing particular plans are discussed. Apart from that changes in the thematic-content structure of the monthly issue have been presented as well as opinions and evaluations given by its readers and members of the editorial board have been cited.
“Continents – New Mercury” (January 1959 – February 1961)
Keywords: "Kontynenty - Nowy Merkuriusz"; druga emigracja; prasa literacka - historia